Novel players in the aging synapse: impact on cognition - Temido Ferreira, Mariana (2022)
© Mariana Temido-Ferreira, et al. 2019; Published by Mary Ann Liebert, Inc. This Open Access article is distributed under the terms of the Creative Commons Attribution Noncommercial License ( http://creativecommons.org/licenses/by-nc/4.0/) which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and the source are cited.